Historical wallpapers: the writing on the wall (Bulletin KNOB, 2003)
The aim of the Foundation for Historical Wallpapers and Wall decorations in the Netherlands SHBW is to give greater publicity to the beauty and value of historical wallpapers, to increase knowledge in this field and thus to stimulate conservation.The SHBW manages and opens up a large collection of used wallpapers, which was built up over many years. In a general sense the SHBW is asking attention for historical wallpapers, which are still regularly found in old houses, but are also delicate and may easily disappear during renovations and refurbishments.With an exhibition in Hilversum and the book ‘Achter het behang. Vierhonderd jaar wanddecoratie in het Nederlandse binnenhuis’ a solid foundation was laid for further research and activities. Knowledge is gathered and spread in various ways, e.g. by a newsletter published twice a year, by organising excursions to houses all through the Netherlands, and by providing specific information, expertise and advice.